Dark Septate Endophytic Fungi Help Tomato to Acquire Nutrients from Ground Plant Material - Vergara, Carlos; Araujo, Karla E. C.; Urquiaga, Segundo; Schultz, Nivaldo; Balieiro, Fabiano de Carvalho; Medeiros, Peter S.; Santos, Leandro A.; Xavier, Gustavo R.; Zilli, Jerri E. (Frontiers in Microbiology, 2017)
Dark septate endophytic (DSE) fungi are facultative biotrophs that associate with hundreds of plant species, contributing to their growth. These fungi may therefore aid in the search for sustainable agricultural practices. However, several ecological functions of DSE fungi need further clarification. The present study investigated the effects of DSE fungi inoculation on nutrient recovery efficiency, nutrient accumulation, and growth of tomato plants fertilized with organic and inorganic N sources. Two experiments were carried out under greenhouse conditions in a randomized blocks design, with five replicates of tomato seedlings grown in pots filled with non-sterile sandy soil. Tomato seedlings (cv. Santa Clara I-5300) inoculated with DSE fungi (isolates A101, A104, and A105) and without DSE fungi (control) were transplanted to pots filled with 12 kg of soil which had previously received finely ground plant material (Canavalia ensiformis [L.]) that was shoot enriched with 0.7 atom % 15N (organic N source experiment) or ammonium sulfate-15N enriched with 1 atom % 15N (mineral N source experiment). Growth indicators, nutrient content, amount of nitrogen (N) in the plant derived from ammonium sulfate-15N or C. ensiformis-15N, and recovery efficiency of 15N, P, and K by plants were quantified 50 days after transplanting. The treatment inoculated with DSE fungi and supplied with an organic N source showed significantly higher recovery efficiency of 15N, P, and K. In addition, the 15N, N, P, K, Ca, Mg, Fe, Mn, and Zn content, plant height, leaf number, leaf area, and shoot dry matter increased. In contrast, the only positive effects observed in the presence of an inorganic N source were fertilizer-K recovery efficiency, content of K, and leaf area when inoculated with the fungus A104. Inoculation with A101, A104, and A105 promoted the growth of tomato using organic N source (finely ground C. ensiformis-15N plant material).